2019
DOI: 10.1002/mrd.23305
|View full text |Cite
|
Sign up to set email alerts
|

Tauroursodeoxycholic acid acts via TGR5 receptor to facilitate DNA damage repair and improve early porcine embryo development

Abstract: DNA damage associated with assisted reproductive technologies is an important factor affecting gamete fertility and embryo development. Activation of the TGR5 receptor by tauroursodeoxycholic acid (TUDCA) has been shown to reduce endoplasmic reticulum (ER) stress in embryos; however, its effect on genome damage responses (GDR) activation to facilitate DNA damage repair has not been examined.This study aimed to investigate the effect of TUDCA on DNA damage repair and embryo development. In a porcine model of ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 40 publications
(81 reference statements)
0
11
0
Order By: Relevance
“…TUDCA may activate TGR5-mediated signaling to reduce DNA damage and improve embryo development after ultraviolet light exposure [9]. The effects of TUDCA on insulin secretion were mimicked by the specific TGR5 agonist INT-777 [10].…”
Section: Introductionmentioning
confidence: 99%
“…TUDCA may activate TGR5-mediated signaling to reduce DNA damage and improve embryo development after ultraviolet light exposure [9]. The effects of TUDCA on insulin secretion were mimicked by the specific TGR5 agonist INT-777 [10].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the secondary bile acids deoxycholic acid and taurochenodeoxycholic acid were increased in DF 1.75 gilts compared with DF 1.0 gilts. Tauroursodeoxycholic acid was shown to facilitate DNA damage repair and improve early embryo development in pigs [ 55 ] and other mammals [ 56 ]. Additionally, DF intake also altered levels of other metabolites, including spermidine [ 57 ], 4-aminobenzoic acid [ 58 ] and ibuprofen [ 59 ] that are known to influence oocyte quality or reproductive function.…”
Section: Discussionmentioning
confidence: 99%
“…Because studies have reported that insufficient repair of DNA damage inhibited embryonic development. 57 Thus, DBDPE reduces PN size and increases DNA damage by interfering with nuclear F-actin assembly. Zygotic nuclear F-actin is critical for embryonic development because F-actin is assembled in the PN of mouse zygotes, and perturbation of zygotic nuclear F-actin dynamics leads to dysregulation of genes associated with genome integrity and abnormal embryonic development in mice.…”
Section: Discussionmentioning
confidence: 99%